The European IPF registry (eurIPFreg): baseline characteristics and survival of patients with idiopathic pulmonary fibrosis - Guenther, Andreas; Krauss, Ekaterina; Tello, Silke; Wagner, Jasmin; Paul, Bettina; Kuhn, Stefan; Maurer, Olga; Heinemann, Sabine; Costabel, Ulrich; Barbero, María Asunción Nieto; Müller, Veronika; Bonniaud, Philippe; et al. (My University, 2018)
BACKGROUND: Since 2009, IPF patients across Europe are recruited into the eurIPFreg, providing epidemiological data and biomaterials for translational research.METHODS: The registry data are based on patient and physician baseline and follow-up questionnaires, comprising 1700 parameters. The mid- to long-term objectives of the registry are to provide clues for a better understanding of IPF phenotype sub-clusters, triggering factors and aggravating conditions, regional and environmental characteristics, and of disease behavior and management.RESULTS: This paper describes baseline data of 525 IPF subjects recruited from 11/2009 until 10/2016. IPF patients had a mean age of 68.1 years, and seeked medical advice due to insidious dyspnea (90.1%), fatigue (69.2%), and dry coughing (53.2%). A surgical lung biopsy was performed in 32% in 2009, but in only 8% of the cases in 2016, possibly due to increased numbers of cryobiopsy. At the time of inclusion in the eurIPFreg, FVC was 68.4% +/- 22.6% of predicted value, DLco ranged at 42.1% +/- 17.8% of predicted value (mean value +/- SD). Signs of pulmonary hypertension were found in 16.8%. Steroids, immunosuppressants and N-Acetylcysteine declined since 2009, and were replaced by antifibrotics, under which patients showed improved survival (p = 0.001).CONCLUSIONS: Our data provide important insights into baseline characteristics, diagnostic and management changes as well as outcome data in European IPF patients over time.TRIAL REGISTRATION: The eurIPFreg and eurIPFbank are listed in ClinicalTrials.gov(NCT02951416).
Keywords: idiopathic pulmonary fibrosis (IPF); European registry for idiopathic pulmonary fibrosis (eurIPFreg); interstitial lung diseases (ILD); ddc:610